2015
DOI: 10.1080/01916599.2014.1002971
|View full text |Cite
|
Sign up to set email alerts
|

Friedrich Hayek and Michael Polanyi in Correspondence

Abstract: FriedrichHayek and Michael Polanyi corresponded with each other for the best part of thirty years. They had shared interests that included science, social science, economics, epistemology, history of ideas and political philosophy. Studying their correspondence and related writings, this article shows that Hayek and Polanyi were committed Liberals but with different understandings of liberty, the forces that endanger liberty, and the policies required to rescue it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Interpreters (Scott-Moleski 2005, Nye 2011, Jacobs-Mullins 2015, Beira 2016, Bíró 2019 agree that, for Polanyi, the film was not only a tool representing economic ideas. It was also a way of inducing large-scale social change.…”
Section: Towards the First Versionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interpreters (Scott-Moleski 2005, Nye 2011, Jacobs-Mullins 2015, Beira 2016, Bíró 2019 agree that, for Polanyi, the film was not only a tool representing economic ideas. It was also a way of inducing large-scale social change.…”
Section: Towards the First Versionmentioning
confidence: 99%
“…Some reviewers suggested that there were basic inconsistencies in Polanyi's proposal. He and Mullins (2015). Previous studies about the two were mostly concerned about finding out who should be seen as the reanimator of the concept of spontaneous order.…”
Section: From Film To Bookmentioning
confidence: 99%
“…Despite this account, Polanyi and Hayek were rarely (Allen 1998) seen as brothers-in-arms by contemporaries. The complexity of their partly joined but partly separated endeavors to save liberalism has been treated in the illuminating study by Struan Jacobs and Phil Mullins (2015). Previous studies about the two were mostly concerned about finding out who should be seen as the reanimator of the concept of spontaneous order.…”
Section: From Film To Bookmentioning
confidence: 99%
“…Previous studies about the two were mostly concerned about finding out who should be seen as the reanimator of the concept of spontaneous order. Some scholars argued that Polanyi recoined the concept for modern neoliberal narratives (Jacobs 1997(Jacobs , 1999(Jacobs , 2015. Others argued that it was Hayek who did much of the recoining (Caldwell 2004;Bladel 2005).…”
Section: From Film To Bookmentioning
confidence: 99%
“…Polanyi (1948) used the term ‘spontaneous order’ before Hayek, although earlier precedents stretch back to John Stuart Mill and others (Bladel, 2005; D'Amico, 2015; Jacobs, 2000; Jacobs and Mullins, 2016). Polanyi was influenced by related phenomena in chemistry and physics.…”
Section: Polanyi Hayek and The Mont Pèlerin Societymentioning
confidence: 99%